Chinese Knot Inspired Ag Nanowire Membrane for Robust Separation in Water Remediation. Issue 11 (20th April 2018) - Xiong, Zhu; Li, Tiantian; Liu, Fu; Lin, Haibo; Zhong, Yun; Meng, Qing'an; Fang, Qile; Sakil, Habib; Song, Weijie
Abstract: Chinese knot is a "traditional handicraft art" in Chinese culture, which is expected to ward off evil spirits and pray for good luck. It is constructed by weaving cords and tying different types of knots firmly. Inspired by Chinese knot, a robust 1D Ag nanowire membrane with nanoscale knots is fabricated to achieve robust catalytic/anti‐bacterial separation. Silver mirror reaction is manipulated to anchor Ag nanowires on a hierarchical polyvinylidene fluoride membrane substrate. The robust Ag nanowire membrane withstands the vigorous cross‐flow hydraulic shear (3000 mL min −1 ) for 24 h at 0.1 MPa without any physicochemical deterioration. The Chinese knot inspired membrane exhibits extraordinary robustness in continuous catalysis, "kill‐release" anti‐bacteria, oil‐in‐water emulsion, and ultrafiltration separation. This work paves a new way for constructing a robust 1D inorganic nanowire membrane for water remediation applications. Abstract : A Chinese knot inspired Ag nanowire membrane is designed to achieve robust catalytic/anti‐bacterial separation in water remediation. Both polyvinylidene fluoride micro/nanostructures and Ag nanoknots play a crucial role in firmly anchoring the Ag nanowire layer. The Chinese knot inspired membrane paves a new way for multipurpose membrane applications in catalysis, energy storage, and separation.